Are Working Time Accounts Beneficial for German Establishments? - Lutz Bellmann; Olaf Hübler (Institute for the Study of Labor (IZA), 2015)
This contribution investigates whether working time accounts are beneficial for the performance of German establishments. Based on the representative German Establishment Panel of the Institute for Employment Research during the period 2008-2013, effects on productivity, wages, sales, firm size, investments, further training, labor mobility, working hours, operating surplus and profits as performance indicators are estimated. Heterogeneity and robustness are investigated by a subgroup analysis where we distinguished between establishments with a high and a low share of qualified workers, between firms with strong and weak sales fluctuations. Additionally, different lengths of the agreed compensation period and reasons for longer time out periods of the employees are considered. Unobserved firm effects as well as interdependencies between important performance indicators and working time accounts are analyzed. OLS estimates, Lewbel's instrumental estimator and IV panel approaches are applied. As major results we find that productivity and investments are positively correlated with working time accounts. No significant effects of working time accounts can be detected on wages, the number of employees and operating surplus of IV panel estimates. However, on average, we find a tendency towards negative effects on profits. This result is less likely in establishments with a high share of skilled workers. Under strong sales fluctuations we find positively significant on the operating surplus. These mixed results hint to a conflict between the employers and employees interests concerning working time accounts that result in compromise solutions.
Keywords: C22; D21; J21; J22; 330; sales fluctuations; share of qualified workers; flexible working time; working time accounts; productivity; establishments; wages; labor mobility; operating surplus; profits; compensation period